Perfluorocarbon-Loaded Hydrogel Microcapsules from Interface Shearing for Magnetic Guided Ultrasound and Laser Activation - Zhu, Zhiqiang; Zhang, Ming; Zhu, Yuanqing; Huang, Fangsheng; Si, Ting; Xu, Ronald X. (Frontiers in Physics, 2020)
Stimuli-responsive microcarriers have received considerable attention in a variety of fields, including disease diagnosis, drug delivery, sensing and imaging. Here, we report the generation of multiple-responsive perfluorocarbon-loaded magnetic hydrogel microcapsules (PMHMs) with uniform size for magnetic controlled ultrasound (US) and laser activation. The PMHMs are fabricated by a novel coaxial interface shearing (CIS) method based on the mechanism of liquid bridge formation and fracture. Perfluorocarbon and iron oxide magnetic nanoparticles (MNPs) are used as US-responsive and photothermal absorption medium respectively, and MNPs are also used for magnetic-controlled targeting. Moreover, the size, structure, and function of the prepared biocompatible PMHMs can be precisely controlled by adjusting the process parameters of CIS. It is indicated that the PMHMs have different US- and light-responsive characteristics, mainly because of the difference of their activation mechanisms. It is demonstrated that laser has better activation resolution and can achieve site-specific activation and drug release of PMHMs. The multiple-responsive features imply that the PMHMs fabricated by CIS may provide an effective drug release platform for biomedical and pharmaceutical applications.